2013
DOI: 10.1557/opl.2013.203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of γ-radiation on Mechanical Properties of Model UK Nuclear Waste Glasses

Abstract: The effect of -radiation on the mechanical properties of model UK intermediate and high level nuclear waste glasses was studied up to a dose of 8 MGy. It was determined thatirradiation up to this dose had no measurable effect upon the Young's modulus, shear modulus, Poisson's ratio, indentation hardness, or indentation fracture toughness. The absence of measurable radiation induced changes in mechanical properties was attributed to redox mediated healing of electron-hole pairs generated by -irradiation by mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Radioactive cesium is one of the high-level waste elements of concern, which results from neutron-induced fission reactions of nuclear fuels . The Cs isotopes are β-emitters, which can result in high levels of radiogenic heating, and one of the few crystalline matrices that are considered for its immobilization are hollandite-type oxides …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioactive cesium is one of the high-level waste elements of concern, which results from neutron-induced fission reactions of nuclear fuels . The Cs isotopes are β-emitters, which can result in high levels of radiogenic heating, and one of the few crystalline matrices that are considered for its immobilization are hollandite-type oxides …”
Section: Introductionmentioning
confidence: 99%
“…1 The Cs isotopes are βemitters, which can result in high levels of radiogenic heating, and one of the few crystalline matrices that are considered for its immobilization are hollandite-type oxides. 10 Compounds adopting the hollandite-type structure crystallize in a tetragonal unit cell (I4/m). 11 The hollandite structure, nominally A 2 B 8 O 16 , consists of a chain of B 3+ octahedra linked via corner and edge-sharing, where the A-and B-site cations can be disordered over the two crystallographically distinct sites.…”
Section: Introductionmentioning
confidence: 99%
“…4,9,11,13,14 It has been recently demonstrated that the presence of transition metals (e.g., Fe) in the borosilicate glass can lead to an increased resistance to structural defects caused by β-particles or γ-rays. [23][24][25][26] The release of β-particles and γ-rays from radioactive elements can lead to the formation of electron-hole pairs, which can result in a change in the silicate and borate bonding networks. 23,25 Previous reports have suggested that Fe present in the glass matrix can trap the electron-hole pairs because of the redox characteristics of this element.…”
mentioning
confidence: 99%
“…[23][24][25][26] The release of β-particles and γ-rays from radioactive elements can lead to the formation of electron-hole pairs, which can result in a change in the silicate and borate bonding networks. 23,25 Previous reports have suggested that Fe present in the glass matrix can trap the electron-hole pairs because of the redox characteristics of this element. 23,25 Rare-earth titanate pyrochlore-type crystalline oxides have been considered as potential nuclear wasteforms because the crystal structure of these materials can incorporate actinides, with natural samples having been found to contain up to 30 wt% UO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation